1978
DOI: 10.1016/0033-5894(78)90025-x
|View full text |Cite
|
Sign up to set email alerts
|

Late Cenozoic Paleoclimates of the Gaap Escarpment, Kalahari margin, South Africa

Abstract: The Gaap Escarpment is a dolomite cuesta demarcating the southeast margin of the Kalahari. Since Miocene-Pliocene times, thick masses of lime tufa have repeatedly accumulated at several points along this escarpment, and four regional sequences are described. These allow discrimination of six major depositional complexes, commonly characterized by basal cryoclastic breccias or coarse conglomerates that reflect frost shattering and torrential runoff, followed by sheets and lobes of tufa generated in an environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(44 citation statements)
references
References 46 publications
1
42
0
Order By: Relevance
“…Such appears to have been the case for the northern Kalahari (Street and Grove, 1976;Grey and Cooke, 1977;Heine, 1978;Cooke, 1980;Cooke and Heine, 1983;Helgren and Brooks, 1983;Helgren, 1984), the south-western Kalahari (Heine, 1981(Heine, , 1982, the central Namib (Vogel and Visser, 1981 ;Lancaster, 1983;Vogel, 1983 ;Ward et al, 1983 ;Heine and Geyh, 1984), the northern and central Transvaal (Marker, 1974), the central interior (Butzer, Stuckenrath et al, 1978;Butzer, Fock et al, 1979;Butzer, 1984aButzer, , 1984b, the Karoo (Beaumont, 1986) and the south-western Cape (Butzer, 1984a). Avery (1979), Beaumont et al (1984, Butzer (1973a, 1984a, 1984b, Butzer, Fock et al (1973, Butzer and Helgren (1972), Butzer, Stuckenrathet al (1978), Coetzee (1967), Cooke (1975Cooke ( , 1980Cooke ( , 1984, Cooke and Heine (1983), Deacon and Brooker (1976), Deacon, H. J. et aL (1984), Deacon, Scholtz and Daitz (1983), , , Grey and Cooke (1977), Heine (1978Heine ( , 1981Heine ( , 1982, …”
Section: -15 O00bpmentioning
confidence: 94%
“…Such appears to have been the case for the northern Kalahari (Street and Grove, 1976;Grey and Cooke, 1977;Heine, 1978;Cooke, 1980;Cooke and Heine, 1983;Helgren and Brooks, 1983;Helgren, 1984), the south-western Kalahari (Heine, 1981(Heine, , 1982, the central Namib (Vogel and Visser, 1981 ;Lancaster, 1983;Vogel, 1983 ;Ward et al, 1983 ;Heine and Geyh, 1984), the northern and central Transvaal (Marker, 1974), the central interior (Butzer, Stuckenrath et al, 1978;Butzer, Fock et al, 1979;Butzer, 1984aButzer, , 1984b, the Karoo (Beaumont, 1986) and the south-western Cape (Butzer, 1984a). Avery (1979), Beaumont et al (1984, Butzer (1973a, 1984a, 1984b, Butzer, Fock et al (1973, Butzer and Helgren (1972), Butzer, Stuckenrathet al (1978), Coetzee (1967), Cooke (1975Cooke ( , 1980Cooke ( , 1984, Cooke and Heine (1983), Deacon and Brooker (1976), Deacon, H. J. et aL (1984), Deacon, Scholtz and Daitz (1983), , , Grey and Cooke (1977), Heine (1978Heine ( , 1981Heine ( , 1982, …”
Section: -15 O00bpmentioning
confidence: 94%
“…The cave was formed in the Oxland Tufa, the youngest parts of which are dated to 230 ± 17 ka by uranium-thorium (Vogel and Partridge, 1984). Butzer et al (1978) stated that the sediments are older than a widespread manganiferous patina. This patina is older than the Blue Pool Tufa II, which has a minimum radiocarbon date of 15,980 ± 230 BP, and younger than the Blue Pool Tufa I, which has uranium-thorium ages ranging from 30 ± 3 to 103 ± 6 ka (Vogel and Partridge, 1984).…”
Section: Comment [Msu35]: Spell Outmentioning
confidence: 99%
“…The patina is also younger than a travertine at Witkrans Cave dated by radiocarbon to a minimum of 33,150 ± 2,500 BP (Berger and Libby, 1966;Clark, 1971). Butzer et al (1978) argued that the dissolution of Equus Cave was contemporary with the formation of the Blue Pool Tufa I. The human remains are thus broadly constrained between a calibrated radiocarbon age of 17,600-16,850 BC and the formation of the Oxland Tufa at 230 ± 17 ka and most likely belong to the period between 103 ± 6 ka and 30 ± 3 ka.…”
Section: Comment [Msu35]: Spell Outmentioning
confidence: 99%
“…van Zinderen Bakker, 1976), it has also been suggested that more extensive Northern Hemisphere ice sheets would have resulted in a southward displacement of the African rainbelt (cf. the Intertropical Convergence Zone (ITCZ)), bringing more tropical rain to the region during the summer (Butzer, 1984;Butzer et al, 1978;Lancaster, 1979;Lewis et al, 2010).…”
Section: Introductionmentioning
confidence: 99%